2020
DOI: 10.1007/s40732-020-00430-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Momentum Theory and Humans: A Review of the Literature

Abstract: Behavioral Momentum Theory (BMT) is often described as analogous to Newton's (1687) laws of motion. That is to say, similar to an object in motion continuing in motion unless acted upon by a force, responses occurring in a static environment will continue to occur at the same rate, unless presented with a disruptor (Nevin, Tota, Torquato, & Shull, Journal of the Experimental Analysis of Behavior, 53, 359-379, 1990). When evaluating response rates through a behavioral momentum framework, responding continuing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…As an illustration, Fisher et al (2019) found that dense baseline schedules of reinforcement were associated with higher magnitudes of resurgence of severe problem behavior than were lean baseline schedules of reinforcement when therapists placed functional communicative responses (FCRs) on extinction. Although studies have shown that BMT predictions fall short of describing relapse phenomena, the model has spurred several lines of research (described below) on clinically viable approaches to relapse mitigation, and conceptual aspects of the model remain useful for directing some components of clinical practice (Craig & Shahan, 2016; Fisher, Greer, Craig, et al, 2018; Fisher, Greer, Fuhrman, et al, 2018; Lambert et al, 2016; Mace et al, 2010; Trump et al, 2021).…”
Section: Quantitative Theories and A Narrative Account Of Relapsementioning
confidence: 99%
“…As an illustration, Fisher et al (2019) found that dense baseline schedules of reinforcement were associated with higher magnitudes of resurgence of severe problem behavior than were lean baseline schedules of reinforcement when therapists placed functional communicative responses (FCRs) on extinction. Although studies have shown that BMT predictions fall short of describing relapse phenomena, the model has spurred several lines of research (described below) on clinically viable approaches to relapse mitigation, and conceptual aspects of the model remain useful for directing some components of clinical practice (Craig & Shahan, 2016; Fisher, Greer, Craig, et al, 2018; Fisher, Greer, Fuhrman, et al, 2018; Lambert et al, 2016; Mace et al, 2010; Trump et al, 2021).…”
Section: Quantitative Theories and A Narrative Account Of Relapsementioning
confidence: 99%
“…Data from behavioral persistence studies designed according to the Behavioral Momentum framework are diverse but do not exhaust all contingencies that organisms may be exposed to, especially when it comes to humans. For instance, little attention has been given to the role of verbal control on behavioral persistence (see Trump et al, 2021). To our knowledge, Podlesnik and Chase (2006) is the only study that investigated the influence of verbal control on resistance to change through a Behavioral Momentum framework (for a review of how instructions can affect behavior sensitivity under other frameworks, see Kissi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the suppressive effects of both response‐dependent point loss and response force have been reported, neither has been evaluated in the context of BMT, which requires a relative assessment of the effects of the disruptive events (Craig et al, 2014; Grace, 2018; Luiz et al, 2019; Trump et al, 2021). Given the applicational importance of response‐reduction procedures and the paucity of research on these procedures in relation to BMT, the present experiments were designed to assess the relative persistence of differentially reinforced responding of humans as a function of point‐loss contingency and response force.…”
mentioning
confidence: 99%